2002
DOI: 10.1152/japplphysiol.00568.2001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in hepatic gene expression in a rat model of ethanol-induced liver injury

Abstract: . Sex differences in hepatic gene expression in a rat model of ethanol-induced liver injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…In downregulatory genes Lsdh and CYP2C11 expression were reduced as expected after ethanol consumption (Figure 4; Tadic et al, 2002;Deaciuc et al, 2004a). Thus, similar results of alcohol related gene expression were obtained employing two independent detection techniques and established that ethanol exposure elicits stable changes in gene expression both in primary hepatocytes culture as well as liver invivo (present study and Deaciuc et al, 2004a,b).…”
Section: Ethanol Induced Changes In Genes Expressed In Liversupporting
confidence: 86%
See 3 more Smart Citations
“…In downregulatory genes Lsdh and CYP2C11 expression were reduced as expected after ethanol consumption (Figure 4; Tadic et al, 2002;Deaciuc et al, 2004a). Thus, similar results of alcohol related gene expression were obtained employing two independent detection techniques and established that ethanol exposure elicits stable changes in gene expression both in primary hepatocytes culture as well as liver invivo (present study and Deaciuc et al, 2004a,b).…”
Section: Ethanol Induced Changes In Genes Expressed In Liversupporting
confidence: 86%
“…Nearly 35% of genes expressed in liver exhibit more than two fold changes in the presence of ethanol (Deaciuc et al, 2004a). Using same gene chip approach, other studies have confirmed a similar trend of alcohol induced gene expression (Tadic et al, 2002;Deaciuc et al, 2004b;French et al, 2005). To validate this ethanol sensitivity we selected four genes; two genes that are upregulated, [Alcohol dehydrogennase-1 (Adh-1) and GlutathionS-transferase Yc2 (GST-Yc2)], and two genes that are downregulated, [L-serine dehydratase (Lsdh) and Cytochrome P450 2C11 (CYP2C11)], by ethanol (Tadic et al, 2002;Park et al, 2005).…”
Section: Ethanol Induced Changes In Genes Expressed In Livermentioning
confidence: 55%
See 2 more Smart Citations
“…Interestingly, gender-specific gene expression in the mouse brain is found at an embryonic stage that precedes the production of sex hormones [17]. Other cases of gender divergence in gene expression include the hepatic response to ethanol consumption in rats [18], and the sensitivity of murine hematopoietic stem cells to benzene intoxication [19]. An example of gender difference in the heart includes the genomic response to pressure overload, a condition in which male mice show a more robust over-expression of genes involved in immunity and inflammation than females [20], which is in agreement with the more pronounced inflammatory response found in male mice after MI as described here by Fang et al [2].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%